Bilateral renal agenesis/hypoplasia/dysplasia (BRAHD): postmortem analysis of 45 cases with breakpoint mapping of two de novo translocations. - Louise Harewood; Monica Liu; Jean Keeling; Alan Howatson; Margo Whiteford; Peter Branney; Margaret Evans; Judy Fantes; David R Fitzpatrick (PLoS ONE)
Background Bilateral renal agenesis/hypoplasia/dysplasia (BRAHD) is a relatively common, lethal malformation in humans. Established clinical risk factors include maternal insulin dependent diabetes mellitus and male sex of the fetus. In the majority of cases, no specific etiology can be established, although teratogenic, syndromal and single gene causes can be assigned to some cases. Methodology/principal findings 45 unrelated fetuses, stillbirths or infants with lethal BRAHD were ascertained through a single regional paediatric pathology service (male:female 34:11 or 3.1:1). The previously reported phenotypic overlaps with VACTERL, caudal dysgenesis, hemifacial microsomia and Müllerian defects were confirmed. A new finding is that 16/45 (35.6%; m:f 13:3 or 4.3:1) BRAHD cases had one or more extrarenal malformations indicative of a disoder of laterality determination including; incomplete lobulation of right lung (seven cases), malrotation of the gut (seven cases) and persistence of the left superior vena cava (five cases). One such case with multiple laterality defects and sirelomelia was found to have a de novo apparently balanced reciprocal translocation 46,XY,t(2;6)(p22.3;q12). Translocation breakpoint mapping was performed by interphase fluorescent in-situ hybridization (FISH) using nuclei extracted from archival tissue sections in both this case and an isolated bilateral renal agenesis case associated with a de novo 46,XY,t(1;2)(q41;p25.3). Both t(2;6) breakpoints mapped to gene-free regions with no strong evidence of cis-regulatory potential. Ten genes localized within 500 kb of the t(1;2) breakpoints. Wholemount in-situ expression analyses of the mouse orthologs of these genes in embryonic mouse kidneys showed strong expression of Esrrg, encoding a nuclear steroid hormone receptor. Immunohistochemical analysis showed that Esrrg was restricted to proximal ductal tissue within the embryonic kidney. Conclusions/significance The previously unreported association of BRAHD with laterality defects suggests that renal agenesis may share a common etiology with heterotaxy in some cases. Translocation breakpoint mapping identified ESRRG as a plausible candidate gene for BRAHD.